7
$\begingroup$

One form of Stolz-Cesaro that is well known states:

If $(a_n)$ and $(b_n)$ are real sequences such that $b_n \uparrow \infty$ and $(a_{n+1} - a_n)/(b_{n+1} - b_n)$ converges as $n \to \infty$, then

$$ \lim_{n \to \infty} \frac{a_{n+1} - a_n}{b_{n+1} - b_n} = L \in \mathbb{R} \cup\{\pm \infty\} \,\, \implies \,\, \lim_{n \to \infty}\frac{a_n}{b_n} =L$$

It is perhaps not so well known that a reverse implication is true when an additional condition is imposed:

$$ \lim_{n \to \infty}\frac{b_n}{b_{n+1}} = B \in \mathbb{R} \setminus \{1\} , \,\,\,\,\, \lim_{n \to \infty}\frac{a_n}{b_n} = L \,\, \implies \,\,\lim_{n \to \infty} \frac{a_{n+1} - a_n}{b_{n+1} - b_n} = L $$

For a proof note that

$$\frac{a_{n+1} - a_n}{b_{n+1} - b_n} \left(1 - \frac{b_n}{b_{n+1}} \right) = \frac{a_{n+1}}{b_{n+1}} - \frac{a_n}{b_{n+1}} = \frac{a_{n+1}}{b_{n+1}} - \frac{a_n}{b_{n}} \frac{b_n}{b_{n+1}}$$

and, hence,

$$\frac{a_{n+1} - a_n}{b_{n+1} - b_n} = \left(1 - \frac{b_n}{b_{n+1}} \right)^{-1} \left(\frac{a_{n+1}}{b_{n+1}} - \frac{a_n}{b_{n}} \frac{b_n}{b_{n+1}} \right)$$

If $B \neq 1$, the limit on the RHS exists and

$$\lim_{n \to \infty} \frac{a_{n+1} - a_n}{b_{n+1} - b_n} = (1- B)^{-1}(L - L B) = L$$

If $B = 1$, then counterexamples to the reverse implication are readily found.

The question is what additional conditions are needed for the reverse Stolz -Cesaro theorem to hold in the case where $B = 1$?

$\endgroup$
3
$\begingroup$

This might be too artificial, but I think it is required to do this.

In view of the counterexample $a_n=n+(-1)^n$, $b_n=n$, we see that $$ b_n/b_{n+1} \rightarrow 1, \ \ a_n/b_n \rightarrow 1 \ \ \textrm{ as }n\rightarrow\infty. $$ This gives $$ \frac{a_{n+1}-a_n}{b_{n+1}-b_n} = \frac{1+(-1)^n(-1-1)}1 $$ and it does not converge. Moreover, this example has the property that $$ c_n=a_n-1 \cdot b_n = (-1)^n, \ \ $$ then $c_{n+1}-c_n$ does not converge.

This suggests that we must have an additional condition that the sequence $$ c_n = a_n - Lb_n $$ satisfies $$ \frac{c_{n+1}-c_n}{b_{n+1}-b_n} \rightarrow 0 \ \textrm{ as } n\rightarrow \infty. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.